2016
DOI: 10.18287/jbpe16.02.040309
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of albumin-fullerenol interaction using laser correlation spectroscopy: the algorithm

Abstract: Abstract.A new algorithm for the solution of the inverse problem of laser correlation spectroscopy is proposed. The algorithm allows the analysis of nanoparticle sizes in polydisperse solutions. Experimental results of the albumin-fullerenol interaction study demonstrating the efficiency of our approach are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Such biological liquids as blood serum and plasma, saliva, solutions of complement proteins, albumin, thrombin, various amino acids and also magnetic liquids were investigated [5]. Polydisperse size distributions of nanoparticles in the biological fluids were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Such biological liquids as blood serum and plasma, saliva, solutions of complement proteins, albumin, thrombin, various amino acids and also magnetic liquids were investigated [5]. Polydisperse size distributions of nanoparticles in the biological fluids were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…The studies have demonstrated that they have clinical applications as carriers to transport drugs across the brain and ocular barriers [ 18 ]. In the work of Nepomnyashchaya et al, it is also shown that fullerenol can be used as a probing substance for the analysis of structural changes in proteins [ 19 ].…”
Section: Introductionmentioning
confidence: 99%